Aurorasaurus: A citizen science platform for viewing and reporting the aurora. Issue 9 (7th September 2015) - MacDonald, E. A.; Case, N. A.; Clayton, J. H.; Hall, M. K.; Heavner, M.; Lalone, N.; Patel, K. G.; Tapia, A.
Abstract A new, citizen science‐based, aurora observing and reporting platform has been developed with the primary aim of collecting auroral observations made by the general public to further improve the modeling of the aurora. In addition, the real‐time ability of this platform facilitates the combination of citizen science observations with auroral oval models to improve auroral visibility nowcasting. Aurorasaurus provides easily understandable aurora information, basic gamification, and real‐time location‐based notification of verified aurora activity to engage citizen scientists. The Aurorasaurus project is one of only a handful of space weather citizen science projects and can provide useful results for the space weather and citizen science communities. Early results are promising with over 2000 registered users submitting over 1000 aurora observations and verifying over 1700 aurora sightings posted on Twitter.